SCoT, ISSR, and SDS-PAGE Investigation of Genetic Diversity in Several Egyptian Wheat Genotypes under Normal and Drought Conditions - Abdelghany S. Shaban; S. A. Arab; Mostafa M. Basuoni; Mahmoud S. Abozahra; Aisha M. Abdelkawy; M. M. Mohamed (International Journal of Agronomy)
Using agronomic parameters, ISSR (inter simple sequence repeat), and SCoT (start codon targeted) markers, ten potential wheat genotypes were examined for genetic diversity under normal and drought conditions. Significant agronomic features have been identified, as well as a low drought susceptibility index. Using seven SCoT and seven ISSR primers, a total of 112 amplified DNA fragments were synthesized, resulting in 61 and 51 bands, respectively. For SCoT and ISSRs, the percentage of polymorphism was 93.4% and 78.4%, respectively. Two markers, ISSR and SCoT, were found to be effective in detecting polymorphism among the examined genotypes, with mean PIC values of 0.61 and 0.62, respectively. In terms of marker index (MI), resolving power (Rp), and polymorphism percentage, SCoT markers exhibited the most significant values. The examination of seed storage proteins revealed 21 subunits with a mass ranging from 22 to 110 kDa. A cluster analysis of the data and morphological features contributed to identifying different molecular and biochemical bands that could be linked to genotype 4’s drought-resistance capabilities.